2013
DOI: 10.1007/s00540-013-1704-7
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight pentastarch is more effective than crystalloid solution in goal-directed fluid management in patients undergoing major gastrointestinal surgery

Abstract: HES 70/0.5 exerted larger volume effects than did crystalloid under nonspecific conditions. However, similar volume effects were observed during volume loss and extensive sympathetic blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
3
10
1
Order By: Relevance
“…It appears that people undergoing major gastrointestinal surgery benefit most from HES over crystalloids. 131 Similar results have been shown in pigs undergoing major abdominal surgery. 132,133 Furthermore, HES show better restoration of splanchnic microcirculation than isotonic saline.…”
Section: Perioperative Fluid Challengesupporting
confidence: 73%
See 1 more Smart Citation
“…It appears that people undergoing major gastrointestinal surgery benefit most from HES over crystalloids. 131 Similar results have been shown in pigs undergoing major abdominal surgery. 132,133 Furthermore, HES show better restoration of splanchnic microcirculation than isotonic saline.…”
Section: Perioperative Fluid Challengesupporting
confidence: 73%
“…Differences between elective surgical and critically ill or septic patients include physiological–pharmacological (different aspects of Starling's equation, predisposition of AKI through primary disease state) and therapeutic (treatment duration and cumulative dose) parameters, and can explain their divergent outcomes. It appears that people undergoing major gastrointestinal surgery benefit most from HES over crystalloids . Similar results have been shown in pigs undergoing major abdominal surgery .…”
Section: Indications Considerations and Recommendations For The Usesupporting
confidence: 69%
“…The use of colloids has been suggested to counteract this undesired volume overload, but studies evaluating the volume effects of HES in people have shown conflicting results. The administration of HES was found to improve hemodynamic parameters (ie, stroke volume index) in a group of patients undergoing gastrointestinal surgery necessitating a fluid challenge . Controversially, other studies evaluating stroke volume optimization in patients undergoing orthopedic surgery failed to demonstrate differences between HES and crystalloids in fluid challenge responses .…”
Section: Perioperative Fluid Therapymentioning
confidence: 98%
“…Balanced and unbalanced solutions are compared Kotake et al 32 35 A colloid different from HE 6%: 130/0.4 is used L'Hermite et al 33 56 Does not include complications or mortality as primary result Dehne et al 34 60 A colloid different from HE 6%: 130/0.4 is used. GDFT is not performed Godet et al 35 65 GDFT is not performed Guo et al 36 42 A colloid different from HE 6%: 130/0.4 is used.…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%